Cytomegalovirus (CMV) seropositivity decreases B cell responses to the influenza vaccine. Issue 12 (17th March 2015) - Frasca, Daniela; Diaz, Alain; Romero, Maria; Landin, Ana Marie; Blomberg, Bonnie B.
Highlights Influenza vaccination is less effective in CMV-seropositive individuals. B cell biomarkers of optimal vaccine responses are reduced by CMV-seropositivity. CMV-seropositivity is associated with increased intrinsic inflammation in B cells.